Excessive amount of rainfall decreases oil palm yield on well-drained peatland. Issue 1 (February 2021) - Marwanto, S; Hendri, J; Salwati,
Abstract: Low inputs of smallholder plantation in drained peatland causes the low oil palm yield. Extreme environmental factors in tropics, such as excessive rainfall, may also reduce the yield. The research objective was to evaluate the effect of the amount of rainfall on oil palm fresh fruit bunch (FFB) yield. Two study sites with different drainage condition of well (WD) and fair (FD) drained oil palm plantations on peatland was carried out from 2018 to 2019 in Jambi Province, Indonesia. The daily rainfall was monitored using a manual rain gauge. FFB yield was monitored every two weeks, following the farmer's practice. This study showed that the excessive amount of rainfall in WD plantation site decreased FFB yield in the subsequent weeks after the rainfall events. The higher the amount of rainfall the longer the recovery of FFB yield occurs. The lowering FFB yield was possibly affected by nutrient deficiency due to nutrient transportation through water movement during the event of high rainfall amount. The FFB yield in the FD site was not affected by rainfall, reflected the higher nutrient availability of FD compared to that of WD. Based on these findings, it is confirmed that well-drained agricultural peatland is a fragile ecosystem in terms of nutrient loss.